(untitled) (Global Journal of Science Frontier Research, 2018)
Here the concept of "TRUE" is defined according to Alfred Tarski, and the concept "OCCURING EVENT" is derived from this definition. From here, we obtain operations on the events and properties of these operations and derive the main properties of the CLASSICAL PROBABILITY. PHYSICAL EVENTS are defined as the results of applying these operations to DOT EVENTS. Next, the 3 + 1 vector of the PROBABILITY CURRENT and the EVENT STATE VECTOR are determined. The presence in our universe of Planck’s constant gives reason to presume that our world is in a CONFINED SPACE. In such spaces, functions are presented by Fourier series. These presentations allow formulating the ENTANGLEMENT phenomenon.